Structural systematics in isomorphous binary cocrystal solvates comprising 2,2′-dithiodibenzoic acid, 4-halobenzoic acid and dimethylformamide (1 : 1 : 1), for halide = chloride, bromide and iodide - Tan, Sang Loon *; Lo, Kong Mun *; Tan, Yee Seng *; Tiekink, Edward R. T. * (Royal Society of Chemistry, 2022)
The 1:1:1 binary co-crystal solvates formulated as 2,2'-dithiodibenzoic acid (DTBA), 4-halobenzoic acid (4-XBA) and dimethylformamide (DMF) for X = Cl (1), Br (2) and I (3) are isomorphous and the supramolecular association in this series has been probed by a wide range of computational chemistry techniques. The common feature of the molecular packing is the formation of robust three-molecule aggregates sustained by a non-symmetric {···HOC=O}2 synthon, formed between DTBA and 4-XBA, and a DTBA-hydroxyl-O–H···O(carbonylDMF) hydrogen bond (with a reciprocating DMF-C–H···O(carbonyl-DTBA) contact). Supramolecular tapes are evident and feature DTBA-C–H···O(DMF), DTBA-C–H···S(DTBA), DMF-O···π(DTBA-phenyl) and DMF-C–H···π(DTBA-phenyl) contacts. The point-to-point connections between tapes are of the type π(4-XBA-phenyl)···π(DTBA-phenyl), π(4-XBA-phenyl)···π(4-XBA-phenyl), DTBA-C–H···π(DTBA-phenyl) and DMF-C···X